Reposisi Teologi Zakat dalam Praksis Pengentasan Kemiskinan - Suripto (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2015)
Praxis of zakat in Islam as the implementation of the three pillars need to be repositioned in order to be useful in establishing the benefit of the individual and social well-being. Since orders are mandatory zakat in Islam is essentially a form of distribution for economic justice among fellow Muslims in order to avoid a gap between the rich and the poor. Model distribution of zakat which has been traditionally managed should be immediately changed by using modern management so that the right target and can actually help alleviate poverty (recipients) of poverty, so that they can be turned into tax payers. Although the charity is an individual responsibility, but the state also has a responsible management. Then the State should establish a special agency to manage zakat trustful and professional and must be administered separately from the government budget.